Dynamic exepectation theory: Insights for market participants - Bodo Herzog (Journal of Risk and Financial Management, 2019)
This paper develops a new methodology in order to study the role of dynamic expectations. Neither reference-point theories nor feedback models are sufficient to describe human expectations in a dynamic market environment. We use an interdisciplinary approach and demonstrate that expectations of non-learning agents are time-invariant and isotropic. On the contrary, learning enhances expectations. We uncover the "yardstick of expectations" in order to assess the impact of market developments on expectations. For the first time in the literature, we reveal new insights about the motion of dynamic expectations. Finally, the model is suitable for an AI approach and has major implications on the behaviour of market participants.
Keywords: D84; D83; C61; Y80; 330; expectation theory; information theory; AI; risk management; financial dynamics; neuroeconomics; econopyhsics